(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background India continues to be a country with a high burden of tuberculosis. Tuberculous lymphadenitis is one of the commonest manifestations of extra pulmonary tuberculosis. The aim of this study was to find the commonest cause of superficial lymphadenopathy and to describe the various cytological patterns of tuberculous lymphadenitis. Materials and Methods This was a cross sectional study conducted between June 2022 and September 2023. All patients with superficial lymphadenopathy were included in the study. All slides were stained with H & E, PAP and MGG. Acid fast staining for tubercular bacilli was done on smears with cytological features of tuberculosis and in all cases where pus was aspirated. Results A total of 300 aspirations were done. Maximum aspirates were blood mixed material (81.6%). 144 cases were of tubercular lymphadenitis with cervical group of lymph nodes (75.6%) being the commonest location. Maximum cases of tubercular lymphadenitis were in the age group of 21-30 years (36) and showed a female preponderance (75). Out of the 144 cases 43.75% showed AFB positivity on ZN stain. Epithelioid cell granuloma with necrosis was the commonest cytological pattern seen (41.7%) and showed maximum AFB positivity. Minimum AFB positivity was seen with smears showing caseous necrosis only. Conclusions Superficial lymphadenopathy is one of the commonest indications for FNAC and tuberculosis is the commonest etiology in our region. Coupled with ZN staining a reliable and early diagnosis of tuberculous lymphadenitis can be given avoiding a biopsy. In patients where AFB is not demonstrated on ZN staining, a microbiological confirmation could be sought for diagnosis.